BP Blowout : Inside the Gulf Oil Disaster. - Jacobs, Daniel (Brookings Institution Press, 2016)
The inside story of the worst environmental disaster in American history. Blowout is the first comprehensive account of the legal, economic, and environmental consequences of the April 2010 blowout at a BP well in the Gulf of Mexico. The accident destroyed the Deepwater Horizon oil rig and killed eleven people. The resulting offshore oil discharge, the largest ever in the United States, polluted much of the Gulf for months, wreaking havoc on its inhabitants. A former Justice Department lawyer responsible for enforcing environmental laws, Daniel Jacobs tells the story that neither BP nor the fe.